Design of N‐Type Textured Bi2Te3 with Robust Mechanical Properties for Thermoelectric Micro‐Refrigeration Application. Issue 6 (29th December 2022) - Zhu, Yu‐Ke; Jin, Yifan; Zhu, Jianbo; Dong, Xingyan; Liu, Ming; Sun, Yuxin; Guo, Muchun; Li, Fushan; Guo, Fengkai; Zhang, Qian; Liu, Zihang; Cai, Wei; et al.
Abstract: Thermoelectric refrigeration is one of the mature techniques used for cooling applications, with the great advantage of miniaturization over traditional compression refrigeration. Due to the anisotropic thermoelectric properties of n‐type bismuth telluride (Bi2 Te3 ) alloys, these two common methods, including the liquid phase hot deformation (LPHD) and traditional hot forging (HF) methods, are of considerable importance for texture engineering to enhance performance. However, their effects on thermoelectric and mechanical properties are still controversial and not clear yet. Moreover, there has been little documentation of mechanical properties related to micro‐refrigeration applications. In this work, the above‐mentioned methods are separately employed to control the macroscopic grain orientation for bulk n‐type Bi2 Te3 samples. The HF method enabled the stabilization of both composition and carrier concentration, therefore yielding a higher quality factor to compare with that of LPHD samples, supported by DFT calculations. In addition to superior thermoelectric performance, the HF sample also exhibited robust mechanical properties due to the presence of nano‐scale distortion and dense dislocation, which is the prerequisite for realizing ultra‐precision machining. This work helps to pave the way for the utilization of n‐type Bi2 Te3 for commercial micro‐refrigeration applications. Abstract : Commonly used methods for increasing the preferred orientation of n‐type Bi2 Te3 include liquid phase hot deformation (LPHD) and traditional hot forging (HF). This work, as an insightful understanding of the HF method, discloses the intrinsic mechanisms of both superior thermoelectric and robust mechanical properties, aiming to shed light on texture engineering utilized for viable micro‐refrigeration applications.